Deuteride Materials - Liu, Jiping; Liu, Xiaobo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This is the very first book that offers an up-to-date and comprehensive overview on deuteride. It not only includes the concept, existing forms, key characteristics, but also reviews the preparation and characterization technologies and the latest research developments of deuteride. The special properties such as the nuclear properties, isotropic and neutron effect, poisonousness, radioactivity, volume expansion are systematically discussed to build up the sound understanding of the materials. In particular, this work reviews a number of commercial and scientific uses of the materials including nuclear reactors, NMR spectroscopy and medicines. Researchers and industrial professionals in medicine, chemistry, biochemistry, environmental sciences and defense sciences will benefit from this work.
Element Deuterium -- Fundamentals of Deuterides -- Preparation, Identification and Characterization of Deuterides -- Metal-Deuteride -- Applications of Deuteride -- Summary and Future Prospects.
Keywords: Chemistry, Technical; Thermodynamics; Materials -- Analysis; Security systems; Spectrum analysis; Industrial Chemistry; Thermodynamics; Characterization and Analytical Technique; Security Science and Technology; Spectroscopy